Multiple calcium channels regulate neurotransmitter release from vagus nerve terminals in the cat bronchiole - Fujisawa, Kanichiro (1999)
1. Twitch-like contractions and non-adrenergic non-cholinergic (NANC) relaxations evoked by electrical field stimulation (EFS) of the cat bronchiole were used to examine the voltage-activated calcium channels involved in excitatory and inhibitory neurotransmission in the cat bronchiole. 2. Nifedipine (50 μM), the L-type calcium channel antagonist, did not affect the twitch-like contraction and NANC relaxations. However, low concentrations of the N-type calcium channel blocker ω-conotoxin GVIA (ω-CgTX GVIA) (0.1 μM) irreversibly abolished twitch-like contractions evoked by trains of EFS ⩽10 stimuli at 20 Hz. 3. After the prolonged treatment with 0.1 μM ω-CgTX GVIA, EFS evoked initial fast and later slow NANC relaxations in the presence of 5-HT (10 μM), atropine and guanethidine (1 μM each). However increased concentration of ω-CgTX GVIA (1 μM) completely suppressed the slow NANC relaxation without affecting the initial fast component. 4. ω-agatoxin IVA (100 nM), the P- and Q-type calcium channel inhibitor, and nimodipine (10 μM), the L- and T-type calcium channel blocker, did not affect the amplitude of the initial fast NANC relaxation in the absence or presence of ω-CgTX GVIA (1 μM). 5. The contraction or relaxation induced by exogenous acetylcholine (ACh) (0.5 μM) or the nitric oxide donor, s-nitroso-N-acetyl penicillamine (SNAP) (1 μM) were not affected by ω-CgTX GVIA (1 μM). 6. Taken together, these results suggest that generation of twitch-like contraction and later slow NANC relaxation are regulated by N-type calcium channels, whereas generation of the initial fast NANC relaxation possibly involves R-type calcium channel.